Formulation of bio‐based epoxy foams from epoxidized cardanol and vegetable oil amine. Issue 11 (29th July 2015) - Dworakowska, Sylwia; Cornille, Adrien; Bogdał, Dariusz; Boutevin, Bernard; Caillol, Sylvain
Abstract : This article deals with the synthesis of new bio‐based epoxy foams from the reaction between cardanol‐derived epoxy compounds and vegetable oil‐derived diamines. Cardanol is a natural alkylphenol obtained from Cashew Nut Shell Liquid (CNSL), an abundant non‐edible by‐product of the cashew nutshell industry. Curing of epoxy monomers proceeded by reaction with Priamine 1073 diamine. Poly(methylhydrogenosiloxane) was used as blowing agent in order to expand epoxy material. Bio‐based epoxy foams were formulated with different amounts of blowing agent and were characterized by scanning electron microscopy, dynamic mechanical analysis, thermal analysis, and by measurement of their apparent density. The foams exhibited good thermal stability above 210°C and glass transition temperatures around 20°C. Obtained materials can be considered as promising low cost and environmentally friendly foams for structural applications. Practical applications: The reactant described in this article, i.e., epoxidized cardanol from CNSL, provides bio‐based aromatic building blocks for further epoxy foam syntheses by reaction with vegetable oil‐derived amine and blowing agent. The obtained rigid epoxy foams are partially bio‐based and may be applied as shock, thermal and vibration insulation, and for the production of lightweight materials for the transportation industry such as aircraft‐interior panels and crash pads. This paper proposes new epoxy foams from cardanol epoxy and fatty amines. Abstract : This paper proposes new epoxy foams from cardanol epoxy and fatty amines.